(untitled) (Global Journal of Human-Social Science, 2023)
The need to break with the monoculture of an epistemology of knowledge produced and transmitted within the Brazilian educational environment requires the urgency of an epistemic rupture that is dominant and has colonial bases Based on this this article proposes a change in practices based on an epistemic rupture with decoloniality as the educational principle to be addressed and incorporated in Brazilian education to overcome inequalities elucidating the need for and importance of this paradigm for the teaching of race-ethnic relations for the valorization of African history and culture For this this article at first deduces how the coloniality modernity was established to invalidate all knowledge not belonging to Europe advancing to the importance of educational policies aimed at education for ethno-racial relations exposing a criticism of the production of knowledge in the university leading to the notes towards the construction of a decolonial pedagogy based on transgression freedom and criticality The need to break with the monoculture of an epistemology of knowledge produced and transmitted within the Brazilian educational environment requires the urgency of an epistemic rupture that is dominant and has colonial bases Based on this this article proposes a change in practices based on an epistemic rupture with decoloniality as the educational principle to be addressed and incorporated in Brazilian education to overcome inequalities elucidating the need for and importance of this paradigm for the teaching of race-ethnic relations for the valorization of African history and culture For this this article at first deduces how the coloniality modernity was established to invalidate all knowledge not belonging to Europe advancing to the importance of educational policies aimed at education for ethno-racial relations exposing a criticism of the production of knowledge in the university leading to the notes towards the construction of a decolonial pedagogy based on transgression freedom and criticality